2020
DOI: 10.1002/mgg3.1526
|View full text |Cite
|
Sign up to set email alerts
|

Variable degree of mosaicism for tetrasomy 18p in phenotypically discordant monozygotic twins—Diagnostic implications

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
0
11
1
Order By: Relevance
“…Interestingly, in most reports, blood is the source of DNA for genetic testing, thus relative scarcity of reported genetic differences between monozygotic twins may be due to blood chimerism caused by vascular anastomoses in monochorionic placentas (Chen et al, 2013) which may mask a relevant genetic differences (Armitage et al, 2021; Erlich, 2011). Indeed, in our previous study, we also showed the usefulness of nonblood‐derived DNA (hair follicles and buccal mucosa) in genetic analysis of phenotypically discordant monozygotic twins (Rydzanicz et al, 2021). Thus, we strongly suggest that blood may not be the optimal tissue to search for genetic differences between monozygotic twins.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…Interestingly, in most reports, blood is the source of DNA for genetic testing, thus relative scarcity of reported genetic differences between monozygotic twins may be due to blood chimerism caused by vascular anastomoses in monochorionic placentas (Chen et al, 2013) which may mask a relevant genetic differences (Armitage et al, 2021; Erlich, 2011). Indeed, in our previous study, we also showed the usefulness of nonblood‐derived DNA (hair follicles and buccal mucosa) in genetic analysis of phenotypically discordant monozygotic twins (Rydzanicz et al, 2021). Thus, we strongly suggest that blood may not be the optimal tissue to search for genetic differences between monozygotic twins.…”
Section: Introductionmentioning
confidence: 80%
“…DNA from 30 hair follicles (I‐2 and I‐3) and buccal mucosa (III‐5) was extracted using the DNA IQ™ Casework Pro‐Kit for Maxwell® 16 (Promega, Madison, WI). Twins (I‐2, I‐3) monozygosity was confirmed using a forensic STR panel as previously described (Rydzanicz et al, 2021). Whole exome sequencing (WES) was performed for I‐2, I‐3, and III‐3 using 50 ng of genomic DNA extracted from hair follicles (I‐2, I‐3) or blood (III‐3) with SureSelectQXT Reagent Kit combined with SureSelectXT Human All Exon v5 (Agilent Technologies, Cedar Creek, TX).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Genotyping data was analyzed using Nexus Copy Number software version 10.0 (BioDiscovery). Quality control of samples was performed as described previously 14,50 . Briefly, samples with Log R Ratio (LRR) sd >0.2 were flagged as poor quality and excluded from the analysis.…”
Section: Snp Array Genotyping Was Performed For Um and Pt Samples On An Illumina Infiniummentioning
confidence: 99%